(untitled) (Research, Society and Development, 2020)
Chemical dependency is considered a public health problem in today’s society or that highlights the importance of using therapeutic occupation techniques. The objective of the research was to evaluate the participation in vegetable cultivation practices, as well as in environmental education and in stimulating the recovery of drug addicts in the city of Breves, PA. The work was developed at the Center for the Recovery of Chemical Dependents “Passion for Souls: Casa do Ouleiro.”In this place, there was an explanation about the respect for the work theme. Food production need sand proposal to build a vegetable garden were identified; a questionnaire was applied to the interns and an interview with the person responsible for them. Such production practices contributed to the occupation of patients, enabling knowledge about the conservation of the environment and the adoption of eating habits in daily life, through personal, collective responsibility with the exchange of flavors and experiences among themselves. Provide individuals subject to stress, personal and social reintegration, occupation, prevent leisure for long periods, new productive skills, and a possible source of family income. The results pointed to the challenge of discovering changes to stimulate and motivate a change and reestablish the movements of one, be they knowledge, emotional and social so that they are recovered and ready to reinsert themselves in society. , it was possible to encourage practices through the therapeutic garden as a stimulus for the recovery of drug addicts, favoring a better quality of life for individuals in search of sustainable socio-economic development.